ALGORITMA GENERAL VARIABLE NEIGHBORHOOD SEARCH PADA CAPACITATED VEHICLE ROUTING PROBLEM WITH TIME WINDOWS DAN IMPLEMENTASINYA - Ulil Ilmi Fadila; Sapti Wahyuningsih; Darmawan Satyananda (UNIVERSITAS NEGERI MALANG, 2022)
The Capacitated Vehicle Routing Problem with Time Windows (CVRPTW) is one of the variants of the Vehicle Routing Problem (VRP), which is the problem of determining the optimal route from the depot to the consumer which is located spread out with different requests. In CVRPTW problem solving considers capacity and time constraints. Determining the optimal route can reduce costs and energy spent during the distribution process. The General Variable Neighborhood Search (GVNS) algorithm can be applied to the CVRPTW problem. The GVNS algorithm is an improvement on the VNS algorithm using RVND. The GVNS algorithm starts with finding the initial solution, continues with perturbation, and then the repair procedure is carried out. Perturbation and improvements to the GVNS algorithm are performed repeatedly according to the predetermined IterMax. The GVNS algorithm for CVRPTW will be implemented using the Borland Delphi 7.0 programming language. The product in the form of this application can be used more practically to solve CVRPTW problems using the GVNS algorithm.Keywords: Capacitated Vehicle Routing Problem with Time Windows (CVRPTW), General Variable Neighborhood Search (GVNS) Algorithm, Randomized Variable Neighborhood Descent (RVND)